The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1439-0531.2009.01352.x
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and Leptin Did Not Improve Meiotic Maturation of Porcine Oocytes CulturedIn Vitro

Abstract: To improve culture system for in vitro maturation (IVM) of porcine oocytes, ghrelin, leptin or growth hormone (GH), at concentration of 0, 0.5, 5, 50 and 500 ng/ml were added to the porcine follicular fluid (pFF)-supplemented medium NCSU23, and their effects on the maturation and cytoskeletal distribution of the oocytes with or without cumulus cells were compared. In the cumulus-denuded oocytes, no significant changes were noted in the maturation rate by different hormone treatments due to a marked decline in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
2
9
2
1
Order By: Relevance
“…These observations confirm previous reports (Xia et al, 1994;Illera et al, 1998;Sirotkin et al, 2000) of stimulatory action of IGF-I on porcine oocyte nuclear maturation. However, they do not correspond to the previous reports of stimulatory action (Craig et al, 2005;Kun et al, 2007) or lack of effect (Jin et al, 2009;Suzuki et al, 2009) of leptin on porcine oocyte maturation. Furthermore, they do not confirm a previous report (Suzuki et al, 2009) of inhibitory action of ghrelin on this process.…”
Section: In Immatured Oocytescontrasting
confidence: 99%
See 3 more Smart Citations
“…These observations confirm previous reports (Xia et al, 1994;Illera et al, 1998;Sirotkin et al, 2000) of stimulatory action of IGF-I on porcine oocyte nuclear maturation. However, they do not correspond to the previous reports of stimulatory action (Craig et al, 2005;Kun et al, 2007) or lack of effect (Jin et al, 2009;Suzuki et al, 2009) of leptin on porcine oocyte maturation. Furthermore, they do not confirm a previous report (Suzuki et al, 2009) of inhibitory action of ghrelin on this process.…”
Section: In Immatured Oocytescontrasting
confidence: 99%
“…However, they do not correspond to the previous reports of stimulatory action (Craig et al, 2005;Kun et al, 2007) or lack of effect (Jin et al, 2009;Suzuki et al, 2009) of leptin on porcine oocyte maturation. Furthermore, they do not confirm a previous report (Suzuki et al, 2009) of inhibitory action of ghrelin on this process. This is the first demonstration to show leptin can not only promote or influence oocyte maturation, but also it can inhibit oocyte maturation.…”
Section: In Immatured Oocytescontrasting
confidence: 99%
See 2 more Smart Citations
“…However, controversial results have been reported in the literature. In some species, leptin seems to promote rearrangement of cytoskeletal elements (Suzuki et al 2010) that are involved in chromosome segregation and in processes of organelle movement (Sun & Schatten 2006). Other studies have reported that leptin enhances an appropriate spindle assembly during metaphase (Jin et al 2009) and stimulates meiotic oocyte maturation in mouse (Matsuoka et al 1999), pig (Craig et al 2004, Kun et al 2007, Zhang et al 2007) and cattle (Paula-Lopes et al 2007, Van Tol et al 2008.…”
Section: Discussionmentioning
confidence: 99%